2013
DOI: 10.1177/0976399613480879
|View full text |Cite
|
Sign up to set email alerts
|

Globalization, Distance and Disease: Spatial Health Disparities in Rural India

Abstract: More than 50 per cent of the Indian population lives in villages that are located more than five kilometres from the nearest town. This half of India is more likely to experience illnesses of different kinds and simultaneously less likely to get qualified medical treatment. The incidence of premature deaths, infant and child mortality and malnutrition are all significantly higher within villages located further from towns. In consequence, such villagers are more susceptible than others to being overcome by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Furthermore, such scenarios push poor people to even poorer conditions due to overburdening health care expenses. As shown in this study, and in other countries (Chan et al, 2006;Onega et al, 2008;Wang et al, 2008;Luo and Qi, 2009;Wan et al, 2012a) as well as in India (Baru et al, 2010;Krishna and Ananthpur, 2013), the less developed the area, the lesser the spatial accessibility. Disparities between Uttar Pradesh and Bihar were also reflected by Balarajan et al (2011), who have reported higher mortality per 1,000 live-births in Uttar Pradesh compared to Bihar.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Furthermore, such scenarios push poor people to even poorer conditions due to overburdening health care expenses. As shown in this study, and in other countries (Chan et al, 2006;Onega et al, 2008;Wang et al, 2008;Luo and Qi, 2009;Wan et al, 2012a) as well as in India (Baru et al, 2010;Krishna and Ananthpur, 2013), the less developed the area, the lesser the spatial accessibility. Disparities between Uttar Pradesh and Bihar were also reflected by Balarajan et al (2011), who have reported higher mortality per 1,000 live-births in Uttar Pradesh compared to Bihar.…”
Section: Discussionsupporting
confidence: 75%
“…Distance to UA, which is a major constraint to access, had also been identified by Krishna and Ananthpur (2013). In-patient facilities are concentrated in urban or semi-urban areas to maximise profit leading to extra transportation costs for already poor people, while people living in urban areas, who are often better off, have better accessibility and less transportation costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed a severe lack of accessible quality medical assistance following a drowning event. This was consistent with many low-income rural settings, where a lack of transport, long distances to medical facilities and high transport costs prevent families from accessing medical attention in a timely manner (15). As a result, resuscitation was often administered by local people who lacked formal training and abilities.…”
Section: Capacity Building In Low-income Communitiessupporting
confidence: 68%
“…Another is that -despite the support of the programme -institutional deliveries in Gujarat remain associated with large transportation costs, informal payments or other expenses that make programme benefits small relative to the full cost of institutional delivery. 21 Our finding of little or no association between the Chiranjeevi Yojana programme and the out-of-pocket costs of deliveries is more puzzling. Even if the programme failed to make institutional delivery more attractive for any women, it should have reduced the household expenses for the many poor women who still chose institutional delivery.…”
Section: Discussionmentioning
confidence: 85%